Mitigasi Getaran Enclosed High Temperature Flaring System (EHTFS) Berbasis Operational Modal Analysis dan Interaksi Tanah–Struktur - Heri Khoeri; Wisnu Isvara (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2026)
Enclosed High Temperature Flaring Systems (EHTFS) are employed to control gas emissions through high-temperature enclosed combustion; however, structural modifications such as flare stack heightening may alter dynamic characteristics and induce environmental vibration problems. This study evaluates vibration responses induced by EHTFS operation and investigates the mechanisms of vibration amplification and resonance affecting surrounding structures. Field measurements were carried out using three-axis accelerometers installed on the flare stack, supporting structures, soil, and nearby residential buildings during flaring events. Structural dynamic properties were identified using Operational Modal Analysis (OMA) based on the Stochastic Subspace Identification (SSI) method, combined with an assessment of soil–structure interaction. The results show dominant vibration frequencies of 6.1–6.2 Hz, where the natural frequencies of the flare stack and nearby houses are closely spaced. Peak acceleration at residential buildings reached 0.149 m/s², approximately twice that at the source (0.074–0.077 m/s²), indicating significant amplification. Soil investigation revealed shear-wave velocities of 168–257 m/s with relative dynamic amplification factors up to 1.0. Although soil–structure interaction influences wave propagation, the observed amplification is primarily attributed to low-frequency resonance between operational excitation and structural natural frequencies. Increasing flare stack stiffness effectively shifts the natural frequency and reduces resonance potential. The proposed integrated OMA–SSI framework provides a reliable basis for vibration mitigation in industrial flaring facilities.